Effect of whole grain corn on productive performance of fattening turkeys - Paredes, Manuel (2023)
The effect of replacing ground corn with whole grain corn in the finishing phase of the commercial Hybrid Converter turkey was evaluated. A total of male turkeys from 11 to 13 weeks of age were used. Five levels of inclusion of whole corn were evaluated: 0, 25, 50, 75 and 100%. The final weight of the turkeys, body weight gain and the feed conversion rate were not influenced by the levels of inclusion of whole corn, but feed intake was reduced as the turkey consumed higher proportions of whole grain. Likewise, the whole grain at levels of 50, 75 and 100% caused enlargement of the gizzard and liver and decrease in the relative weight of the turkey carcass.